Variation in the oil content in different parts of clove bud and from different geographical regions: Oil content in different parts of clove - Bhosle, Riya; Dighe, Shraddha; Kute, Drushti; Ahuja, Gopaal; Ahuja, Ganesh; Laddha, Kirti (Journal of Spices and Aromatic Crops, 2022)
This study determined the difference in oil content from separated parts of clove buds, full bud with crown, clove bud without crown and dust (stamen and style), and only crown along with dust from market sample. Results showed that the highest oil content in clove bud without a crown. Oil yield varied in clove buds from different geographical regions wherein, Madagascar showed the highest amount of oil.